(3TQM MeGSI CHj JeGes - (3jMji Hf Ydj Hf GdMSf Hf ehSi Hf HSWGe GdNWjH GdJHQjRj GddZhj , CHh RcQjG , J (B502 (3g` s; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s ((3CHh MGeO CMeO Hf eMeO Hf HdGd Hf GdMGQK GdeOfi GdbGjfi s)
(3ChdgG (B:s
(3CeG HYO MeO ddg aEfi cJHJ ddMeGIg TQMkG eSJhai s
(3BNQgG (B:s
(3Ef JSCdi aGdeLO ZjQ GdHOjY bO Md ai Jje heNRhe BNQ cJGH TQM GdMeGSg s
(3fSNI KGfjI GdTQM GdUZjQs
(3hgj eYGQVI heUMMgs
(3hHBNQgG bQGAg SfI (B548 (3g` dCMeO Hf Ydj Hf gHg Gddg Hf eCehf Ydi CHj GdeYGdi CMeO Hf Ydi Hf Ydi Hf GdSejfis
(3hHChdgG Jedc SfI (B609 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
Keywords: (3GdCOHs